Letter (copy)
1936-09-25 WJB/AC/59 International 25th September, 1936. Mr. G. Stolz, International Federation of Trade Unions, 9, avenue d'Orsay, PARIS VII. Dear Comrade Stolz, SPAIN. Mr. Hicks has asked me to write to you stating that at the meeting on Monday he wishes to move a resolution in favour of a deputation being sent from the meeting to Spain. I enclose herewith a copy of the motion, and he thinks that perhaps you will have the necessary translations and copies made, so that those attending may have it before them at the meeting. Yours faithfully, International Department. Resolution. 292/946/10/89